Analisis Partisipasi Perempuan di Sektor Informal - Huzaimi, Fidya Dewi; Arisetyawan, Kukuh (Jurnal Ekonomika : INDEPENDEN, 2023)
The issue of injustice in the treatment of women workers is caused by social norms regarding the division of gender roles. This has an impact on the dominance of women workers in the informal sector. The purpose of this study is to determine the condition of women workers and the factors that influence women's participation in the informal sector. The method used is binary logistic regression, using data from the Indonesian Labor Force Survey (Sakernas) in 2020. The results show that there is a significant influence of the variables of education, marital status, region of residence, and wages on women's participation in the informal sector. Meanwhile, the internet and pre-employment card variables do not show a significant effect. The variables of education and wages have a negative effect, while the variables of marital status and region of residence have a positive effect.